A Perspective on Personalized Therapies in Hypertrophic Cardiomyopathy. Issue 3 (March 2021) - Goldspink, Paul H.; Warren, Chad M.; Kitajewski, Jan; Wolska, Beata M.; Solaro, R. John
Abstract : Abstract: A dominant mechanism of sudden cardiac death in the young is the progression of maladaptive responses to genes encoding proteins linked to hypertrophic cardiomyopathy. Most are mutant sarcomere proteins that trigger the progression by imposing a biophysical defect on the dynamics and levels of myofilament tension generation. We discuss approaches for personalized treatments that are indicated by recent advanced understanding of the progression.